Mimbar Inklusif: Strategi Dakwah Dalam Masyarakat Majemuk - Hespirawati,; Mahmuddin, (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study discusses the concept of the inclusive pulpit as a da’wah strategy in plural societies. Using library research, the study finds that the inclusive pulpit expands preaching spaces from mosques to social media, dialogue forums, and social activities that embrace diversity. Key strategies include dialogical approaches, da’wah bil-hal, humanist language, multicultural education, and interfaith collaboration. The findings reveal that inclusive da’wah helps prevent social friction, reduce stereotypes, and strengthen national unity. The study concludes that its success relies on preachers’ intercultural communication skills, use of digital media, and adaptability to social change